Premarital Sexual Standards among Church Youth Leaders: An Exploratory Study - Glass, J. Conrad (Journal for the scientific study of religion, 1972)
This exploratory study reports findings concerning the premarital sexual standards of a group of teenage United Methodist church leaders from eastern North Carolina. Comparisons are made between these findings and the findings of studies of other samples of young people. Interpretations of the findings are offered and further research questions are proposed.